Incentives and foreign direct investment (UN New YorkUS, 1996)
Provides a conceptual analysis of foreign direct investment incentives; reviews trends in incentives available; and, discusses the influence of incentives on foreign investors' locational choices. Reviews the experience of international mechanisms meant to limit incentives and suggests elements of an international approach.
DC